ASSESSMENT OF MEDICATION ERRORS IN PEDIATRICINPATIENT DEPARTMENT OF A PRIVATE HOSPITAL - Nikhithasri, P.; Ramya, M.; Kishore, P. (International Journal of Current Pharmaceutical Research, 2017)
Objective: To assess the overall rate and incidence of medication errors in pediatric inpatients and to determine the importance of pharmacist participation in medication errors. Methods: A prospective observational study has been conducted in a â€˜private childrens hospital’ for 6 mo at Warangal, Telangana. Patients who are â‰¤18 ywere considered. Data was collected from patient records, direct communication with patient and their care givers. Results: Among 400 patients with 2,461 medication orders,1381(56%) errors were found. Patients were more exposed to AME(33.7) caused by the nursing staff, followed by PME-21.5,CME-0.6,DME-0.2 in incidence with the 95% CI. Conclusion: Pediatric patients are more exposed to administration errors and prescribing errors. Pediatricians and Pharmacists should develop effective programs for safe administration of medications, report medication errors, eliminate barriers in reporting medication errors, encourage a non-punitive reporting culture and create an environment of medication safety for all hospitalized pediatric patients